PKCδ promotes the invasion and migration of colorectal cancer through c-myc/NDRG1 pathway - Jia, Hong-tao; Shao, Yan-fei; Zhou, Xue-liang; Yang, Guang; Huang, Ling; Aikemu, Batuer; Li, Shu-chun; Ding, Cheng-sheng; Fan, Xiao-dong; Hong, Hi-ju; Zhang, Sen; Pan, Rui-jun; et al. (Frontiers in Oncology, 2023)
The therapeutic effect of metastatic colorectal cancer (mCRC) is poor, the unknown metastasis mechanism and targeted drug resistance means that it is important to study the mechanism of invasion and migration of colorectal cancer (CRC) and find new targets.We studied that Protein Kinase C Delta (PKCδ) was overexpressed in multiple tumor tissues and related to tumorigenesis, metastasis, and poor prognosis in CRC. PKCδ could promote Epithelial-Mesenchymal Transition (EMT) and the invasion and migration of CRC in vitro. We confirmed that PKCδ and the tumor suppressor factor N-myc Downstream Regulated Gene 1(NDRG1) had a co-localization relationship in CRC. PKCδ inhibited NDRG1 transcription and protein expression. Overexpressing NDRG1 could inhibit the function of PKCδ in promoting tumor invasion and migration. PKCδ could regulate c-Myc, one transcription factor of NDRG1, to down-regulate NDRG1.Thus, our results showed that PKCδ reduced the expression of NDRG1 through c-Myc, promoting the invasion and migration of CRC through promoting EMT.